Optimalisasi Teknologi Digital Dalam Meningkatkan Branding Dan Penjualan Umkm Roti Sabal Khas Desa Rengas II - Helena Zafira; Khairul Basyar (Surya Edukasi: Jurnal Pengabdian Masyarakat, 2025)
SMEs play an important role in the local economy, including in traditional culinary sectors such as Roti Sabal, which is a signature product of Rengas II Village. However, the main challenge faced by SMEs is the limited marketing and branding capabilities, especially in the digital era. This research aims to analyze how the optimization of digital technology can improve branding and sales for Roti Sabal SMEs in Rengas II Village. The research uses a qualitative approach with interviews and observations of SME actors, as well as secondary data analysis from digital platforms. The results show that the use of digital technologies such as social media, online marketplaces, and digital marketing strategies significantly contribute to increasing product visibility. With the optimization of digital technology, Roti Sabal SMEs in Rengas II Village are not only able to increase sales but also strengthen the product’s identity in a broader market. This study recommends continuous training and mentoring for SME actors to better prepare them for digital competition. With the right strategies, digital technology can be an effective solution in driving the growth of SMEs based on local products